2018
DOI: 10.1111/1756-185x.13394
|View full text |Cite
|
Sign up to set email alerts
|

Target setting for lower limb joint surgery using the Timed Up and Go test in patients with rheumatoid arthritis: A prospective cohort study

Abstract: Objective This prospective observational cohort study aimed to set targets for lower limb joint surgery based on the Timed Up and Go test (TUG), an objective functional outcome measure, in patients with established rheumatoid arthritis (RA). Methods We validated TUG as an outcome measure of lower limb joint surgery and compared it with changes in patient‐reported outcomes, including the Health Assessment Questionnaire Disability Index (HAQ‐DI) and European Quality of life scale with five dimensions (EQ‐5D). Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
0
4
1
Order By: Relevance
“…A potential explanation is that TUG scores after TKA indicated relatively high gait function in the patients in the present study, which might have contributed to a floor effect. Specifically, TUG scores at the 6 months postoperative assessment (mean 8.2 s) were better than the cut-off value of this measure used to represent good physical function after TKA in a previous study (8.8 s) [15]. Therefore, it cannot be concluded that preoperative SB had no significant effect on improvement in TUG scores based on results of the present study.…”
Section: Discussioncontrasting
confidence: 91%
“…A potential explanation is that TUG scores after TKA indicated relatively high gait function in the patients in the present study, which might have contributed to a floor effect. Specifically, TUG scores at the 6 months postoperative assessment (mean 8.2 s) were better than the cut-off value of this measure used to represent good physical function after TKA in a previous study (8.8 s) [15]. Therefore, it cannot be concluded that preoperative SB had no significant effect on improvement in TUG scores based on results of the present study.…”
Section: Discussioncontrasting
confidence: 91%
“…Thirty‐one studies reported utility scores of RA patients 22‐24,34‐42,45,47‐63,65 . The pooled mean EQ‐5D score was 0.66 (95% CI 0.63‐0.69) with high heterogeneity I 2 = 99.65% (Figure 2A).…”
Section: Resultsmentioning
confidence: 99%
“…Thirty-one studies reported utility scores of RA patie nts. [22][23][24][34][35][36][37][38][39][40][41][42]45,[47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63]65 The pooled mean EQ-5D score was 0.66 (95% CI 0.63-0.69) with high heterogeneity I 2 = 99.65% (Figure 2A).…”
Section: Overall Pooling Of Eq-5dmentioning
confidence: 99%
“…The TUG is a performance-based PF measure, known to be valid, reliable, and responsive [44][45][46][47][48][49]. It has also been validated as a useful tool for the evaluation of PF after lower limb joint surgery [50]. TUG evaluates the time required for an individual to stand up from a regular armchair (with a seat height of 46 cm), walk a distance of 3 m, perform a turn, return to the chair and resume sitting [46].…”
Section: Outcome Measuresmentioning
confidence: 99%